Spinal inflammatory hyperalgesia is mediated by prostaglandin E receptors of the EP2 subtype - Reinold, Heiko (American Society for Clinical Investigation, 2005)
Blockade of prostaglandin (PG) production by COX inhibitors is the treatment of choice for inflammatory pain but is also prone to severe side effects. Identification of signaling elements downstream of COX inhibition, particularly of PG receptor subtypes responsible for pain sensitization (hyperalgesia), provides a strategy for better-tolerated analgesics. Here, we have identified PGE(2) receptors of the EP2 receptor subtype as key signaling elements in spinal inflammatory hyperalgesia. Mice deficient in EP2 receptors (EP2(–/–) mice) completely lack spinal PGE(2)-evoked hyperalgesia. After a peripheral inflammatory stimulus, EP2(–/–) mice exhibit only short-lasting peripheral hyperalgesia but lack a second sustained hyperalgesic phase of spinal origin. Electrophysiological recordings identify diminished synaptic inhibition of excitatory dorsal horn neurons as the dominant source of EP2 receptor–dependent hyperalgesia. Our results thus demonstrate that inflammatory hyperalgesia can be treated by targeting of a single PG receptor subtype and provide a rational basis for new analgesic strategies going beyond COX inhibition.